Tanzania : Report on the Observance of Standards and Codes-Data Module, Response by the Authorities, and Detailed Assessments Using Data Quality Assessment Framework. (IMF Staff Country Reports; Country Report ;, 2004)
The data module of this Report on the Observance of Standards and Codes (ROSC) of Tanzania provides a summary assessment of practices on the coverage, periodicity, and timeliness of the data categories against the IMF's General Data Dissemination System (GDDS). It is complemented by an assessment of the quality of national accounts, consumer and producer price indices, and government finance, monetary, and balance-of-payments statistics, using the Data Quality Assessment Framework (DQAF) developed by the IMF's Statistics Department (STA).